Maternal and dietary factors are associated with metabolic syndrome in women with a previous history of gestational diabetes mellitus - Hasbullah, Farah Yasmin; Mohd Yusof, Barakatun Nisak; Abdul Ghani, Rohana; Mat Daud, Zulfitri ‘Azuan; Appannah, Geeta; Abas, Faridah; Shyam, Sangeetha (MDPI AG, 2022)
While it is known that women with a previous history of gestational diabetes mellitus (post-GDM) have a higher risk of metabolic syndrome (MetS), evidence of lifestyle practices from low- and middle-income countries (LMICs) is still scarce. This study aimed to determine the factors associated with MetS in women post-GDM. This cross-sectional study involved 157 women post-GDM (mean age 34.8 ± 5.6 years) sampled from Selangor, Malaysia. We collected data on sociodemographic characteristics and obstetric history. Food intake was assessed using a food frequency questionnaire, and dietary patterns were derived from principal component analysis. MetS was diagnosed according to the 2009 Harmonized criteria. The prevalence of MetS in this study was 22.3%. Western dietary pattern consumption was correlated with MetS, body mass index (BMI), waist circumference, and triglyceride levels. Independent factors associated with MetS were lower education level (odds ratio, OR 4.017, p = 0.007), pre-pregnancy BMI (OR 1.192, p = 0.002), and Caesarean delivery (OR 3.798, p = 0.009). The study identified the maternal and dietary factors associated with MetS in women post-GDM in Malaysia. Community-based interventions that include dietary modification are warranted to prevent MetS and its complications, thus helping to reduce the overall disease burden.